Relationships among corporate website quality, visitor satisfaction and visitor loyalty / Voon Boo Ho and Sandra Rangai Balang - Voon, Boo Ho; Rangai Balang, Sandra (Faculty of Business Management, 2010)
This study aimed to examine how corporate website quality will affect the visitor satisfaction and loyalty. Besides, the role of frequency of visit was also investigated to understand its influences on the relationships between the three variables. The key website quality attributes that significantly distinguished the satisfied and non-satisfied website visitors were also identified. The research was based on survey data. The instrument adapted dimensions mainly proposed by Aladwani and Palvia (2002) and 7-point Likert scale was used. The questionnaire was validated by experts and pre-tested in a pilot survey. The actual survey was conducted by trained enumerators, where 1200 usable questionnaires were gathered from 400 respondents (400 x 3) from various places in Malaysia using quota sampling. The websites evaluated were selected using purposive sampling from companies listed on the Bursa Malaysia. Exploratory factor analysis was used to assess the measures and results indicated that the measurement was reliable and valid. Further statistical analyses included relevant descriptive analyses, independent sample T-test, ANOVA, multiple regression and logistic regression analyses. The results indicated that there were positive relationships among website quality, visitor satisfaction and visitor loyalty. It was found that the relationship between website quality and visitor loyalty was higher with the existence of visitor satisfaction. The logistic regression analysis suggested that some of the website quality items significantly distinguished the satisfied and non-satisfied website visitors. The findings signified that customization, easy access, minimum pages, sufficient information, providing frequently asked question (FAQ), website attractiveness, proper multimedia and creativity were the critical determinants of satisfaction.